El crecimiento del ser personal. - VARGAS, ALBERTO I. (Studia Poliana, 2019)
This paper presents the distinction between organic, esential and personal growth. Based on Leonardo Polo's thought, hope and gift are proposed as the growth logic of the personal act of being and God as the absolute originating growth.